Probabilistic Seismic Safety Assessment of Railway Embankments - Mohammadreza Mohammadi; Araliya Mosleh; Mehran S. Razzaghi; Pedro Alves Costa; Rui Calçada (Applied Sciences, 2023)
The purpose of this research is to study the seismic performance of railway embankments through a probabilistic approach. Nonlinear response history analyses were conducted utilizing PLAXIS software. Three categories of railway embankments were selected and more than 2400 embankment-earthquake case studies were performed. Sensitivity analyses were implemented to obtain the most important variables in the seismic performance of railway embankments. Finally, analytical fragility curves were generated in terms of the mechanical properties of railway embankments (e.g., soil cohesion and friction angle). Fragility functions were developed, employing an incremental dynamic analysis approach using a set of ground motions, including near- and far-field earthquakes. The maximum vertical displacement of the embankment was chosen as a damage index parameter. Fragility curves were derived for three damage states, including slight, moderate and extensive damage, with respect to threshold values proposed in the literature. The results of this study revealed that the mechanical properties of embankments could be considered one of the crucial uncertainty factors in seismic fragility analysis of railway embankments.